Design of Cashier Information System and Sales of Jaya Putra 04 Store Based on Website Using Waterfall Method - Muhamad Bakhar; Zaenal Muttaqin; Ulil Albab (West Science Information System and Technology, 2024)
In the digital era, the need for effective and efficient information systems has become increasingly important to support business operations. This study aims to design and develop a web-based cashier information system for Toko Jaya Putra 04 using the Waterfall method. The system is designed to address challenges in manual transactions, such as long queues, recording errors, and lack of stock visibility. The research stages include requirements analysis, system design using Unified Modeling Language (UML), implementation with PHP programming language and MySQL database, testing using the Black Box Testing method, and system maintenance. The results show that this cashier information system can improve transaction process efficiency, reduce customer waiting times, and simplify stock management and financial reporting. This system is expected to be further developed with additional features, such as digital payment integration, customer loyalty programs, and enhanced data security. By implementing this system, Toko Jaya Putra 04 can enhance service quality and support more strategic business decision-making.